Tocqueville, equality and individualisation - Tomas Wedin (Lychnos, 2019)
The purpose of this article is to elucidate the Swedish postwar educational landscape by reactivating the French diplomat and proto sociologist Alexis de Tocqueville’s reflections on the promises and challenges of democratic society. Writing in the initial stages of the developing modern society, he addressed challenges of a fundamental character that I maintain can open up new perspectives on the changes of pre-university education from 1945 until today. I activate four closely intertwined ideas from his reflections on democratic society in De la démocratie en Amérique and expound how these analytical categories can be mobilised to discern hitherto overseen aspects of the political reforms around 1990. I emphasise in particular how Tocqueville’s reflections on a specific form of individual-centred equality can enhance our understanding of how a neoliberal logic permeated the educational sphere in particular – and political life more generally – from the 1990s onwards.